Prevalence and factors associated with medication non-compliance among patients with hypertension in a tertiary hospital: a cross-sectional study in Malaysia - Mohamad Yusoff, Nur Hanani; Leong, Joyce Whye Sook; Soo, Man Jun; Ching, Siew Mooi (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Hypertension contributes to major cardiovascular morbidities and mortalities worldwide and medication compliance is crucial in achieving target blood pressure control. This study aimed to determine the prevalence and factors associated with non-compliance towards anti-hypertensive medication in Malaysia. Methods: This is a cross-sectional study among hypertensive patients who were attending the medical outpatient department, Hospital Serdang from March until May 2018. Systematic random sampling was used to recruit patients and a structured self-administered questionnaire was used to collect information. Non-compliance is defined as attaining a score of 26 and below from the Medication Compliance Scale. Data analysis was done using SPSS v. 23. Multiple logistic regression was used to determine the predictors of medication non-compliance among hypertensive patients. Results: A total of 120 respondents were recruited into this study with a response rate of 60.9%. Mean age of the study respondents was 60.82 ± 11.25 years old. They were predominantly female (60.8%), Malay (58.3%) and attained at least secondary educational level (75.0%). The prevalence of non-compliance towards anti-hypertensive medication was 25%. Multiple logistic regression showed that side effects of medication (OR=5.59; 95% CI=1.29-24.21, p=0.021), traditional medications usage (OR=19.19; 95% CI=3.90-94.45, p=<0.001), health advice counsellors (OR=35.31; 95% CI=2.03-35.31, p=0.003) and duration of hypertension (OR=3.38; 95% CI=1.05-10.91, p=0.042) were predictors of non-compliance to anti-hypertensive medications among hypertensive patients Conclusion: Our study reported that those with longer duration of hypertension, suffered from side effect of medication and have experience in usage of traditional medicine are the predictors of medication non-compliance.